Sistem Pendukung Keputusan Seleksi Pelatih Sepakbola Pada PSMS Medan Menerapkan Kombinasi Metode ROC Dan ARAS - Sihombing, Soemarno (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Football coaches are people who are fully trained and guide players in carrying out training. Therefore in determining the feasibility of a trainer is very important. In the world of football, many football club management are not optimal in choosing coaches, as is currently experienced by the PSMS Medan football club, which is experiencing a decline in performance due to coaches who are less able to cultivate bad tactics or strategies so that at this time they are relegated. to the 2nd Caste of the Indonesian League which was previously in the 1st (Main) Indonesian League of Caste. In fact, so far in the process of selecting football coaches, especially at PSMS Medan, it is still being implemented in the form of direct appointments because this method does not sound objective, causing injustice to other candidates who may be better. Therefore, a system is needed to solve this, namely a Decision Support System to make it easier for football club management to determine football coaches and avoid system data calculation errors quickly and more accurately by using the Rank Order Centroid (ROC) method and the combination method. Additive Ratio Assessment (ARAS). From the results of this study, Angelo Alessio (A6) is eligible to become a soccer coach with a score of 1,682 as the first rank.